2000
DOI: 10.1257/jep.14.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Fairness and Retaliation: The Economics of Reciprocity

Abstract: This paper shows that reciprocity has powerful implications for many economic domains. It is an important determinant in the enforcement of contracts and social norms and enhances the possibilities of collective action greatly. Reciprocity may render the provision of explicit incentive inefficient because the incentives may crowd out voluntary co-operation. It strongly limits the effects of competition in markets with incomplete contracts and gives rise to noncompetitive wage differences. Finally, reciprocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
934
3
21

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 2,570 publications
(1,033 citation statements)
references
References 27 publications
39
934
3
21
Order By: Relevance
“…Chimpanzees are retaliatory, in that they are negatively reciprocal (34), at least on a very short time scale, consistent with retribution as a means of discipline in animal societies (2,(22)(23)(24). Retribution did not enforce cooperative behavior through reciprocity in the current experiments likely due in part to the fact that subjects switched roles only once and only after engaging with all others.…”
Section: Resultssupporting
confidence: 65%
“…Chimpanzees are retaliatory, in that they are negatively reciprocal (34), at least on a very short time scale, consistent with retribution as a means of discipline in animal societies (2,(22)(23)(24). Retribution did not enforce cooperative behavior through reciprocity in the current experiments likely due in part to the fact that subjects switched roles only once and only after engaging with all others.…”
Section: Resultssupporting
confidence: 65%
“…In line with the important role of the reciprocity principle in people's behavior (e.g., Fehr & Gächter, 2000), we found that participants generally reacted more positively to confirming feedback from their communication partner than to disconfirming feedback. However, whereas we expected that online communication would intensify both positive and negative responses, only negative responses (to disconfirming feedback) were intensified online.…”
Section: The Effect Of Feedback On the Receiver's Reciprocal Feedbacksupporting
confidence: 83%
“…Reciprocation implies a relationship in which one party responds in kind for a deed (good or bad) by the other party (Fehr & Gächter, 2000). Under PWYW, customers might be reciprocating the behavior of the seller for the product or services they received.…”
Section: Why Do People Pay More Under Pif? Four Possible Accountsmentioning
confidence: 99%